Sistem Pakar Identifikasi Modalitas Belajar Siswa Menggunakan Metode Forward Chaining - Asep Kurniawan; Sumijan; Jufriadif Na’am (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Student learning modalities are important to be identified by teachers and students. Because the success of students in the field of academics is supported by the appropriate student learning modalities. Often occurs in the process of teaching and learning teachers do not know the modalities of student learning so that the material in teaching teachers difficult to accept by students. Appropriate learning modalities that are in accordance with the methods taught by the teacher need to be built in an Expert System. Expert System that is processed in this research is taken from the expertise of teachers of Senior High School Counseling Guidance 1 Tilatang Kamang by using Forward Chaining method. Learning modalities are processed using expert systems created with php programming languages ​​and mysql databases. Furthermore, this expert system can determine the modalities of visual learning, auditory and kinesthetic. The result of testing on this method is able to determine the learning modality in the students with the accuracy and the speed is good. Expert system test results have been able to determine student learning modalities clearly and can already be recommended to help teachers and students in improving the way students learn the right.